The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1063/1.4882863
|View full text |Cite
|
Sign up to set email alerts
|

Structure and energetics of hydrogen-bonded networks of methanol on close packed transition metal surfaces

Abstract: Methanol is a versatile chemical feedstock, fuel source, and energy storage material. Many reactions involving methanol are catalyzed by transition metal surfaces, on which hydrogen-bonded methanol overlayers form. As with water, the structure of these overlayers is expected to depend on a delicate balance of hydrogen bonding and adsorbate-substrate bonding. In contrast to water, however, relatively little is known about the structures methanol overlayers form and how these vary from one substrate to another. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(62 citation statements)
references
References 64 publications
6
56
0
Order By: Relevance
“…This work provides insights for predicting water monomer and dimer diffusion behaviour on general surfaces, as well as guidance for future experiments of water dynamics on surfaces. Extending these findings, we think that the diffusion of other H-bonded clusters on surfaces 58,59 could display peculiar behaviours as a result of strong H-bond, diffusion mechanisms via H-bond rearrangements, and NQEs.…”
Section: Discussionsupporting
confidence: 59%
“…This work provides insights for predicting water monomer and dimer diffusion behaviour on general surfaces, as well as guidance for future experiments of water dynamics on surfaces. Extending these findings, we think that the diffusion of other H-bonded clusters on surfaces 58,59 could display peculiar behaviours as a result of strong H-bond, diffusion mechanisms via H-bond rearrangements, and NQEs.…”
Section: Discussionsupporting
confidence: 59%
“…Combining STM with TPD/R, we demonstrated that excess water is needed to convert methanol to formaldehyde on a Cu(111) surface. Since both water and methanol form hydrogen bonded clusters, the co-adsorption of methanol [44][45][46] and water [47,48] results in methanol-water networks that assist in the dehydrogenation of methanol to methoxy.…”
Section: Resultsmentioning
confidence: 99%
“…48,49 This vdW functional has been shown to perform extremely well in a wide range of molecular adsorption studies. [36][37][38][39] The plane-wave expansion was cut off at 550 eV and a Monkhorst-Pack k-points mesh of 4 x 4 x 1 was used for the slab systems.…”
Section: Methodsmentioning
confidence: 99%